Kirpan Sikh in Indonesian Legal Context - Sinaga, Lestari Victoria; Fernando, Zico Junius; Sidauruk, Jupenris (University of Jember, 2024)
This research delves into the nuanced interplay between religious freedom and legal norms in Indonesia, with a specific focus on the Sikh practice of carrying the kirpan. This ceremonial dagger, integral to Sikh faith and identity, presents a unique challenge within Indonesia's diverse legal and socio-cultural landscape, marked by the country's commitment to Pancasila, which emphasizes religious freedom, unity in diversity, and social justice. By employing a normative juridical approach, this study scrutinizes the tension between the kirpan as a manifestation of religious expression and public safety concerns, utilizing comparative analysis to explore international perspectives and solutions. The investigation reveals a critical need for Indonesia to refine its legal and policy frameworks to more effectively accommodate religious practices like the kirpan. Drawing lessons from countries such as India, the UK, Canada, the US, and Sweden, the research advocates for inclusive legal reforms, enhanced public education, and robust intercultural dialogue. These strategies aim to reconcile the practice of carrying the kirpan with public safety imperatives, reflecting a deeper understanding and respect for religious diversity. The findings underscore the significance of integrating Indonesia's foundational principles of Pancasila into the contemporary discourse on religious freedom and minority rights. The study posits that respecting the kirpan within this ideological framework not only aligns with Indonesia's commitment to diversity and tolerance but also strengthens national unity and social harmony. This research contributes to the broader discourse on balancing religious expression and public safety in pluralistic societies, offering a comprehensive blueprint for policy and legal reforms that honor both religious freedom and collective well-being. It emphasizes the importance of dialogue, education, and legal inclusivity in fostering a society that upholds the dignity and rights of all individuals, irrespective of their religious practices. Keywords: Kirpan, Sikh, Freedom of Religion and Human Rights (FoRB), Criminal Law, Indonesia